LIGNIN FILLED NATURAL RUBBER LATEX COMPOSITES AND ITS UTILIZATION IN RUBBER PRODUCTS - MUSTAFA, ASRUL (2014)
In the development of lignin filled rubber latex composite. rubber wood was prior processed. digested and precipitated using centrifugation to obtain lignin. The acquired lignin was then added into natural rubber latex as filler at varying loading and rubber films were prepared from the lignin filled rubber latex composite by casting using glass mould. The effect of lignin on the oil resistance. tensile strength and morphology of the resulting tilms was investigated via tensile strength measurements. Scanning Electron Microscopy (SEM). Transmission Electron Microscopy (TEM) and Atomic Force Microscopy (AFM). The results showed that oil resistance of rubber latex films was enhanced with the addition of lignin above 2 wt% loading. The obvious increase in tensile strengths occurred at lignin loading at I 0 \\1% and 12 vdYo. where the increase was 60% and 73% respectively.